Design High Gain PHEMT LNA for Wireless Application at 5.8 GHz - Pongot K; Ahmad A; Othman A.R; Zakaria Z; Suaidi M.K; Hamidon A.H; Hamidon J.S (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This research present a design of a higher gain (68.94dB) for PHEMT LNA using an inductive drain feedback technique for wireless application at 5.8GHz. The amplifier it is implemented using PHEMT FHX76LP transistor devices. The designed circuit is simulated with Ansoft Designer SV. The LNA was designed using inductive drain feedback, inductive generation to the source, and the T-network as a matching technique was used at the input and output terminal. The low noise amplifier (LNA) provides a noise figure 0.64 dB and gain (S21) of 68.94 dB. The output reflection (S22), input reflection (s11) and return loss (s12) are -17.37 dB, -15.77 dB and -88.39 dB respectively. The measurement shows the stability were at 4.54 and 3-dB bandwidth of 1.72 GHz. The input sensitivity is -92 dBm exceeded the standards required by IEEE 802.16.